VISUALIZATION OF VARIOUS CHALLENGES, RISK, BARRIERS IN IMPLEMENTATION OF E-GOVERNANCE IN NEPAL - Sant Kumar Verma, Dr. Ajay Kumar Bharti (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
E-governance is an important aspect of developing countries. After adoption of federal structure in Nepal various initiatives has been taken by government of Nepal to implement e-governance in country, but still Nepal is taking behind in implementation of e-governance. Current status of rank on implementation of e-governance and other issues shows that Nepal is far behind from other countries. Also in comparison to others SAARC nation also Nepal is lacking behind. Current rank 2020, in e-governance development index show that Nepal is 132 rank. This paper shows the visualization of various challenges, risk and barriers in implementation of e-governance in Nepal.